Memoria, verdad y ambigüedad. Píndaro y el kairós de los poetas - Sferco, Senda (ARFIL y UNL, 2019)
This paper addresses the issue of temporality linked to the production of memory narratives in ancient Greece, when this task was entrusted to poets and their creation of words. Through a study of Pindar (518 BC - 543 BC) Odes and Epinicia - both, in the context of its emergence as through further philosophical interpretations- plausible stories to form a memory appear linked to a selective act of composition , where the poet decides what events will be worthy of Praise , and which , instead, of Shame. In a context that is assumed complex, consisting of mixed forces, word productions serving a sustaining memory must always overcome the opacity of the confusing circumstances, the irony, and the threat of oblivion. Words, in the voice of the poets, will become the efficacy marks of some kind of economy of the ruth that is already mapping the paradoxal memory of its own history.